Immediate fixed temporization with a natural tooth crown pontic following failure of replantation - Smriti Bhargava; Ritu Namdev; Samir Dutta; Rajkumar Tiwari (Wolters Kluwer Medknow Publications, 2011)
Extracted teeth can be bonded directly to adjacent teeth utilizing a prefabricated composite resin framework reinforced with polyethylene fiber as a noninvasive long-term provisional tooth replacement. This immediate provisional restoration allow for exact repositioning of the coronal part of the extracted tooth in its original intraoral three-dimensional position and thus relieves the apprehension of the patient caused by the sudden loss of an anterior tooth.